Investigating effects of entrepreneurial orientation and management on performance - KWON, Moonju (KDI School, 2016)
This study explores how corporate entrepreneurship affects to organizational performance in private and public sector. In particular, this study investigatesi) how the level of organizational performance differs based on the sectors; ii) howeffects ofentrepreneurial orientation and management differ performance objectives includingsatisfaction with performanceandpublic value orientation;iii) how the effect of entrepreneurialorientation and entrepreneurial management on satisfaction with performance and public value orientation differs public sector from private sector organizations. The results of this study find that according to the sectorsand performance objectives, the different variables of entrepreneurial orientation and management are significant on satisfaction with performanceand public value orientation.This study provides managerial and theoreticalimplications to organizational entrepreneurship. To enhance the organization’s performance, distinctive management strategies should be applied for public sector and private sector as well as considered type of performance objectives.
Thesis(Master) --KDI School:Master of Public Policy,2016